The Long Shadow of the Chinese Cultural Revolution: The Intergenerational Transmission of Education - Xin Meng; Guochang Zhao (Institute of Labor Economics (IZA), 2016)
Between 1966 and 1976, China experienced a Cultural Revolution (CR). During this period, the education of around 17 birth cohorts was interrupted by between 1 and 8 years. In this paper we examine whether, and by how much, this large-scale schooling interruption affected their children's education. We find a strong effect: more interrupted education for parents, less completed education for their children. On average the CR cohort had 2.9 years interrupted education. If they failed to catch up after the CR, this translates to a reduction of 0.87 years of schooling and a 9 percentage points (or 50%) reduction in the probability of completing a university degree for their children relative to the children whose parents did not have interrupted schooling. Our results have strong implications for developing countries prone to long-term conflicts which often adversely affect children's education. As human capital accumulation is one of the main drivers of economic development, these negative schooling shocks affecting current generation education levels will have an impact far beyond the immediate economic development of these war-torn economies and extend to the next generation.
Keywords: I24; I25; N3; 330; Chinese Cultural Revolution; human capital; intergenerational education transmission